KNOWLEDGE MANAGEMENT IN ARTIFICIAL INTELLIGENCE BASED AUTOMATED E-MATERIAL FORMATTING TOOL - Mackare, Kristīne; Jansone, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Knowledge is a critical resource for scientific, academical and technological development. In a time of fast development and growth of a massive amount of information and big data, knowledge management (KM) has a crucial role in creating knowledge from data and information. Knowledge management discipline increases its popularity among other fast-developing disciplines as Artificial Intelligence (AI). It is important to understand how fields of science and technological research and development and knowledge management integrate into each other, cooperate, and support each other. Likewise, understanding theoretical bases in the practical use of knowledge management are crucial for learning and development use. The theoretical part of the publication shortly represents knowledge management theoretical basis. It is followed by a description of the case - artificial intelligence based automated e-material formatting tool development and research accompanying the development of the tool. The result part of the publication systematically represents knowledge management aspects in the case study. There are included knowledge management aspects as components of knowledge management definition, types, theories, approaches and methods in the case study. Thereby, the publication shows the cooperation of disciplines through the scope of the case study and could be used as a sample in the study process to understand and show knowledge management and knowledge management aspects in the research and development process.